2009
DOI: 10.1351/pac-con-08-08-17
|View full text |Cite
|
Sign up to set email alerts
|

High-technology materials based on modified polysaccharides

Abstract: Polysaccharides are abundantly available from farm, forest, and microbial resources. They are used in myriad applications. It has been established in the authors' laboratory that their performance is enhanced considerably on purification, grafting by polyacrylamide (PAM), and subsequent hydrolysis as well as cationization. The most significant performance is enhanced in flocculation where it has been found that the modified polysaccharides outperform existing flocculants in national and international markets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 112 publications
0
33
0
Order By: Relevance
“…Chemical modification of GG has also been studied by many researchers as a method to overcome its inherent deficiencies, such as its facile biodegradability. Singh et al [85] compared the Chemical modification of GG has also been studied by many researchers as a method to overcome its inherent deficiencies, such as its facile biodegradability. Singh et al [85] compared the DR efficiencies of pristine GG, purified GG, and grafted GG in water, as shown in Figure 16.…”
Section: Guar Gummentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical modification of GG has also been studied by many researchers as a method to overcome its inherent deficiencies, such as its facile biodegradability. Singh et al [85] compared the Chemical modification of GG has also been studied by many researchers as a method to overcome its inherent deficiencies, such as its facile biodegradability. Singh et al [85] compared the DR efficiencies of pristine GG, purified GG, and grafted GG in water, as shown in Figure 16.…”
Section: Guar Gummentioning
confidence: 99%
“…Singh et al [85] compared the Chemical modification of GG has also been studied by many researchers as a method to overcome its inherent deficiencies, such as its facile biodegradability. Singh et al [85] compared the DR efficiencies of pristine GG, purified GG, and grafted GG in water, as shown in Figure 16. They found that the grafted GG copolymer combined the robustness of GG and the efficiency of the synthetic PAAM polymer, resulting in enhanced drag reduction efficiency.…”
Section: Guar Gummentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical modification of GG has also been studied by many researchers as a method to overcome its inherent deficiencies, such as its facile biodegradability. Singh et al [85] compared the DR efficiencies of pristine GG, purified GG, and grafted GG in water, as shown in Figure 16. They found that the grafted GG copolymer combined the robustness of GG and the efficiency of the synthetic PAAM polymer, resulting in enhanced drag reduction efficiency.…”
Section: Guar Gummentioning
confidence: 99%
“…23.4). The easy approachability model was proposed by Singh in 1995 [21] and has been discussed in detail later on [16,17,43,46,[67][68][69].…”
Section: Singh's Easy Approachability Modelmentioning
confidence: 99%